Changes In Sub Optimal Soil Nutrient Status By Adding Liquid Organic Fertilizer From Tofu Wastewater And Lemongrass: Perubahan Status Hara Tanah Lahan Sub Optimal Dengan Penambahan Pupuk Organik Cair (Poc) Air Limbah Tahu Dan Serai Wangi - Siti Mutmainah (Agrifarm : Jurnal Ilmu Pertanian, 2020)
This study aims to determine the nutrient levels of Liquid Organic Fertilizer (POC) Wastewater and Lemongrass Wastewater and soil nutrient status sub-optimal land after incubation for 21 days. Sub-optimal land is land that naturally has low productivity, therefore it is necessary to add nutrients in both organic and inorganic fertilizers to change nutrient status in the soil. Organic fertilizer in liquid form is one type of fertilizer that can facilitate the absorption of nutrients. Tofu wastewater has an unpleasant odor, one of the efforts that will be made to reduce the odor is by adding fragrant lemongrass in making liquid organic fertilizer. Based on the results of the study note that the total macro nutrient levels (N + P2O5 + K2O) Liquid Organic Fertilizer Wastewater and Lemongrass Wastewater is 0.17% with a degree of acidity 4.39. Suboptimal soil nutrient status after incubation for 21 days with different concentration treatments namely 10%, 30% and 50% addition of Liquid Organic Fertilizer tofu waste water and lemongrass experience changes in potassium nutrient status at concentrations of 0%, 10 %, 30% and 50%, while the phosphorus changes at concentrations of 30% and 50%, but not nitrogen.